A new deep-sea species of Stilipes Holmes, 1908 (Amphipoda, Amphilochidea, Stilipedidae) from western Mexico - Ortiz, M.; Winfield, I.; Hendrickx, M.e. (Zootaxa, 2026)
A new species of the genus Stilipes Holmes, 1908, is described and illustrated from a single female specimen collected from the SW Gulf of California, Mexico, in 1500 m depth. Stilipes sp. nov. represents the sixth species of this genus worldwide, all documented from 200 to 1060 m depth. Characters that separate the new species from congeners include: head with eyes; first three pereonites subequal in length; presence of a conical subrostral lamina and a vestigial accessory flagellum of antenna 1; 6th coxa forming a very wide, rounded posteroventral lobe; epimeral plate 2 acute, directed posteriorly; epimeral plate 3 rounded; telson length and width subequal. A comparative table of diagnostic characters among species of Stilipes is provided, including the depth range and geographic distribution of each species.